235 Resource Use for Beef Cattle in the North Central Great Plains. (7th May 2021) - Lakamp, Andrew D; Aherin, Dustin; Spencer, Douglas; Larson, Robert; Weaber, Robert L; Bormann, Jennifer M; Rolf, Megan M
Abstract: The sustainability of the beef industry has become a point of national interest, particularly the investment of land and water resources. Our objective was to estimate how much land and irrigation water are required to maintain a simulated Angus cow-calf operation in the North Central Great Plains (NCGP) for an average year. A stochastic model was used, which enabled consideration of biological variation. The model computed 100 iterations of a 24-year timeframe (1995–2018). The simulated herd had 100 breeding females with replacement heifers being retained annually. The nutrients required to maintain a body condition score 5 for each individual animal, adjusting for temperature and physiological state, were calculated. A stocking rate of 3.3 hectares (ha) per cow-calf pair and mature cow weight of 600 kg was set, which is representative of the NCGP. Replacement heifers were assumed to be 65% of mature cow weight and allotted 1.22 ha. Bred heifers were assumed to be 85% of mature cow weight and allotted 1.81 ha. The herd was assumed to be grazing from May 1 to October 31. A supplemented ration of 60% alfalfa and 40% corn was provided if an individual's nutritional needs were not met. Animals were assumed to be delivered a base ration from November 1 to April 30, which consisted of 73% alfalfa, 19% wheat straw, and 8% corn. The amount of irrigation necessary to grow feed was determined by estimating evapotranspiration of each crop then subtracting the amount of precipitation during the growing season. Average crop yield was determined using county level data from the UDSA NASS to estimate how much land would be needed for feed production. Sustaining a 100 head cow-calf herd in the NCGP for an average year requires 103.5 million liters for irrigation, 1288.5 ha for crop production, 357 ha grazing land.